Kajian Karakteristik Lokasi Pedagang Kaki Lima Di Kawasan Pendidikan Gunungpati Di Kota Semarang - Ivandi Pratama Hasibuan; Nany Yuliastuti (Jurusan Perencanaan Wilayah dan Kota, 2016)
Street vendor can be found in downtown city, including education area. That also applies in education area of Semarang, such as Gunungpati Region. The emergence of street vendor in Gunungpati region makes a fairly high density environment which is less in order. To answer this problem, the purpose of this research can be formulated as to identify the characteristics of street vendor location in education area.The target to achieve the goal is to identify the activity and bussiness opportunity of street vendorr, consumer profile, consumer perception in the presence of street vendor, and to formulate the characteristics of the street vendor location around education area in Gunungpati by street vendor and consumer perception. The method of this research uses descriptive quantitative approach, comparative descriptive, frequency distribution and crosstab (cross-tabulations). The data collection method is by primary data in the form of questionnaire, field observation and secondary data in the form of documentation. Sampling method for street vendor population is by using stratified random sampling while the sample for the population of consumer is by using accidental sampling technique. The output produced from this research is to identify the characteristics of street vendor location in education area of Gunungpati influenced characteristics in education area of Gunungpati is affected predominantly by existing primary activities such as education and housing facility.